Tantangan Dalam Mewujudkan Kesetaraan Gender Dalam Pers di Indonesia - Ana Nadhya Abrar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
Bringing about gender equality in press is not easy task. It requires five conditions to be meet simultaneously: (i) amendment of Act No. 40/1999; (ii) serious implementation of Indonesian Journalists Ethics Code; (iii) increase of woman journalists; (iv) stopping discrimination agains women in society; and (v) an atmosphere of gender justice in society.